Relation between Chronic Rhinosinusitis and Gastroesophageal Reflux in Adults: A Systematic Review - Ni Putu Omasih Kiantimi; Komang Sarizki Armidita; I Nyoman Satria Pratama; Made Rara Rusmala Dewi M; A.A Sagung Dewi Nurgitayanti (HM Publisher, 2023)
Background: It is not entirely apparent how chronic rhinosinusitis (also known as CRS) develops. Since the 1970s, medical professionals have debated whether or not gastroesophageal reflux (GOR) could be a factor in the development of certain patients' conditions. The purpose of this research is to the relation between chronic rhinosinusitis and gastroesophageal reflux in adults. Methods: By evaluating the preferred reporting items for systematic review and meta-analysis (PRISMA) 2020 standards, this study demonstrated that it met all of the requirements. This enabled the researchers to ensure that the study was as up to date as feasible. Publications published between 2000 and 2023 were included in the search strategy, which included a variety of electronic reference databases (including Pubmed and SagePub). We did not consider review papers, duplicate publications, or half completed articles. Results: In the PubMed database, the results of our search brought up 133 articles, whereas the results of our search on SagePub brought up 69 articles. The results of the search conducted for the last year of 2000 yielded a total of 20 articles for PubMed and 8 articles for SagePub. In the end, we compiled a total of 21 papers, six of which came from PubMed and three of which came from SagePub. We included nine research that met the criteria. Conclusion: According to the findings of most studies, the number of cases of CRS seen in patients with GERD is around two to three times higher than that seen in the general patient group.